AFFECTIVE AND MOTIVATIONAL FACTORS IN ENGLISH AS A SECOND LANGUAGE IN SPAIN - GARCÍA-SAMPEDRO, MARTA; AGUDO PRADO, SUSANA (Journal of Education Culture and Society, 2020)
Aim. Due to the disappointing results in English oral competence achieved by Spanish students in international and national evaluations, the main aim of this research is to know teachers perceptions on the importance of affective factors and motivation in teaching and learning English in primary and secondary education. It is also essential to know whether these factors help students to improve their oral skills.Method. A qualitative paradigm was utilised in this research in which three focus groups with ten teachers each and a moderator, were organised in two different Teacher Training Faculties (Spain and the United Kingdom). The categories of analysis were previously established according to the research aims.Results and conclusion. The results obtained through the analysis of categories indicated that the participant teachers consider affective factors and motivation as fundamental aspects in the process of teaching and learning a second language. In addition they agreed with prestigious experts on the matter, such as Dörnyei, Ushioda or Chomsky, that these aspects are crucial to improve students' linguistic oral competence. The teachers demonstrate their opinions based on their professional experiences and educational philosophy constituting altogether a valuable bunch of information for other experts and researchers.